TRAF6 directs FOXP3 localization and facilitates regulatory T‐cell function through K63‐linked ubiquitination. (18th March 2019) - Ni, Xuhao; Kou, Wei; Gu, Jian; Wei, Ping; Wu, Xiao; Peng, Hao; Tao, Jinhui; Yan, Wei; Yang, Xiaoping; Lebid, Andriana; Park, Benjamin V; Chen, Zuojia; et al.
Abstract: Regulatory T cells (Tregs) are crucial mediators of immune control. The characteristic gene expression and suppressive functions of Tregs depend considerably on the stable expression and activity of the transcription factor FOXP3. Transcriptional regulation of the Foxp3 gene has been studied in depth, but both the expression and function of this factor are also modulated at the protein level. However, the molecular players involved in posttranslational FOXP3 regulation are just beginning to be elucidated. Here, we found that TRAF6‐deficient Tregs were dysfunctional in vivo ; mice with Treg‐restricted deletion of TRAF6 were resistant to implanted tumors and displayed enhanced anti‐tumor immunity. We further determined that FOXP3 undergoes K63‐linked ubiquitination at lysine 262 mediated by the E3 ligase TRAF6. In the absence of TRAF6 activity or upon mutation of the ubiquitination site, FOXP3 displayed aberrant, perinuclear accumulation and disrupted regulatory function. Thus, K63‐linked ubiquitination by TRAF6 ensures proper localization of FOXP3 and facilitates the transcription factor's gene‐regulating activity in Tregs. These results implicate TRAF6 as a key posttranslational, Treg‐stabilizing regulator that may be targeted in novel tolerance‐breaking therapies. Synopsis: Transcription factor FOXP3 is key for development and function of regulatory T cells (Tregs) subject to both transcriptional and posttranscriptional regulation. K63‐linked ubiquitination of FOXP3 by TRAF6 E3 ligase provides a new mechanism to regulate Treg function. Deletion of TRAF6 in Tregs impairs Treg suppressive function and immune homeostasis and anti‐tumour immunity in mice. TRAF6 catalyses K63‐linked ubiquitination of FOXP3 at Lysine 262. The zinc finger and leucine zipper domains of FOXP3 are required for its TRAF6‐mediated ubiquitination. TRAF6‐mediated K63‐ubiquitination promotes nuclear accumulation of FOXP3 and Tregs function. Abstract : K63‐linked ubiquitination of FOXP3 by TRAF6 E3 ligase controls suppressive Treg functions, immune homeostasis and anti‐tumour immunity in mice.